INDENTIFIKASI TINGKAT KESEHATAN DAN STRES KELELAWAR PEMAKAN BUAH (Cynopterus tithaecheilus) SEBAGAI MAMALIA TERBANG - Rahma, Anisa; Hanadhita, Desrayni; Prawira, Andhika Yudha; Cahyadi, Danang Dwi; Supratikno, Supratikno; Maheshwari, Hera; Satyaningtijas, Aryani Sismin; Agungpriyono, Srihadi (Jurnal Veteriner, 2019)
Hematology value is important to evaluate individual health status . This study was purposed to observe hematological value of male and female of Cynopterus tithaecheilus which has not been reported yet. The study was conducted on 1 6 Cynopterus tithaecheilus (6 adult males, 6 adult females and 4 juvenil ) to study about haematological profile . Blood samples were taken using tuberculin needle and analyzed by hematology analyzer for hematological value. Female Cynopterus tithaecheilus has higher number of white blood cells than male, but the differentiation of white blood cell was not different. Male Cynopterus tithaecheilus has a higher platelet than female. Generally Cynopterus tithaecheilus juvenil has a higher leukocyte and a higher platelet than adult.
Keywords: flying mammals, leukocyte differentiation, platellet, stress indeks